2016
DOI: 10.11607/jomi.4681
|View full text |Cite
|
Sign up to set email alerts
|

Survival of Dental Implants Placed in Grafted and Nongrafted Bone: A Retrospective Study in a University Setting

Abstract: To compare dental implant survival rates when placed in native bone and grafted sites. Additionally, risk factors associated with dental implant loss were identified. This study was based on the hypothesis that bone grafting has no effect on implant survival rates. Materials and Methods: A retrospective chart review was conducted for patients receiving dental implants at the University of Texas, School of Dentistry from 1985 to 2012. Exclusion criteria included patients with genetic diseases, radiation and che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 36 publications
2
33
6
Order By: Relevance
“…However, a statistically significant association between implant failure and bone augmentation was not found in the present study, although other studies have demonstrated more failures in these sites. 33 Tonetti et al 34 have highlighted that bone augmentation may present complications inherent to the implant technique and that implants placed in these areas do not present high long-term survival rates as those placed in natural bone areas.…”
Section: Discussionmentioning
confidence: 99%
“…However, a statistically significant association between implant failure and bone augmentation was not found in the present study, although other studies have demonstrated more failures in these sites. 33 Tonetti et al 34 have highlighted that bone augmentation may present complications inherent to the implant technique and that implants placed in these areas do not present high long-term survival rates as those placed in natural bone areas.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, controversial data on the long‐term survival rates of implants placed in augmented vs. pristine bone have been reported (Chappuis, Cavusoglu, Buser, & von Arx, ; Daubert, Weinstein, Bordin, Leroux, & Flemmig, ; Tran et al., ; Urban et al., ; Visser, Stellingsma, Raghoebar, Meijer, & Vissink, ). For example, while some studies showed comparable outcomes in terms of implant survival rates and crestal bone loss (Chappuis et al., ; Urban et al., ), other studies reported inferior outcomes for implants placed in augmented sites (Daubert et al., ; Tran et al., ; Visser et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Heat and toxic by‐products of cigarette smoking, such as nicotine and carbon monoxide, have been associated with impaired cell proliferation and healing 12 . Evidence has shown an association between smoking and implant‐related parameters, including impaired healing, higher postoperative complications, increased peri‐implant bone loss and failure rate of implants placed in grafted bone, reduced mineral density, and poor papilla regeneration 13–17 . In a recent systematic review, Keenan and Veitz‐Keenan 18 reported higher failure rates, risk of postoperative infections, and CBL in implants placed in smokers compared with non‐smokers.…”
mentioning
confidence: 99%